Peran Peradilan Tata Usaha Negara Dalam Perspektif Fiqh Siyasah Untuk Mewujudkan Pemerintahan Yang Baik - Aji, Aniko; Hafizd, Jefik Zulfikar; Arfan, Am’mar Abdullah (Hutanasyah : Jurnal Hukum Tata Negara, 2025)
Article 9, paragraph (1) of Law No. 30 of 2014 on Government Administration stipulates that every decision and/or action taken by administrative officials must be based on statutory regulations and the General Principles of Good Governance (AAUPB). However, in practice, this provision is often disregarded by government officials, leading to abuse of authority. With the enactment of Law No. 30 of 2014, the authority of the State Administrative Court (PTUN) has expanded—not only to annul State Administrative Decisions but also to examine and determine whether there is an element of abuse of authority by government officials. As an independent judicial institution, PTUN plays a strategic role in overseeing the actions of administrative officials, ensuring that its authority is optimized to establish good governance based on AAUPB principles. The findings of this study indicate that the Role of the State Administrative Court in Establishing Good Governance from the Perspective of Fiqh Siyasah (A Case Study of PTUN Semarang) has been well-implemented by PTUN Semarang in accordance with the provisions of Law No. 30 of 2014 and the facts observed in the field.